Pengaruh Penerapan Model Pembelajaran Project Based Learning (PJBL) Terhadap Kemampuan Pemecahan Masalah Spltv Peserta Didik Kelas X - Priska M. Humapi; John R. Wenas; Anetha L. F. Tilaar (Departement of Mathematics Education, 2024)
The ability to solve problems is essential in math learning activities. It is required to have a learning model that can improve the students' SPLTV problem-solving abilities. This research aims to determine whether the students's SPLTV problem-solving abilities that have been taught by the learning model of Project-Based Learning are higher than the students's thinking with a Conventional Learning Model. This research has been conducted in SMA Negeri 3 Bitung by using a population of tenth graders in the school year 2023/2024. It is divided into four classes, and the total is 133 students. The sample selected in this research is from two classes, which are Class X E1 and Class X E3. The total of the students by each classes are 33 students and 34 students.The results of post-test participants in experiment classes and control classes are used as data on their problem-solving abilities. The result explained that the students's SPLTV problem-solving abilities, which use the PjBL Learning Model, are 81,48. This shows a higher average than the students that have been taught by the Conventional Learning Model, which is 65,53. To the full extent of 0.05. Accordingly, the implementation of the PjBL Learning model has an effect on the students' SPLTV problem-solving abilities.